Additive Benefits of β-Alanine Supplementation and Sprint-Interval Training. Issue 12 (December 2016) - BELLINGER, PHILLIP M.; MINAHAN, CLARE L.
ABSTRACT: Purpose: The present study investigated the effects of β-alanine supplementation only, and in combination with sprint-interval training (SIT), on training intensity, and energy provision and performance during exhaustive supramaximal-intensity cycling and a 4- and 10-km time trial (TT). Methods: Fourteen trained cyclists (V˙O2max = 4.5 ± 0.6 L·min −1 ) participated in this placebo-controlled, double-blind study. Subjects performed a supramaximal cycling test to exhaustion (equivalent to 120% V˙O2max ) and a 4- and 10-km TT and 4 × 1-km sprints at three time points: before and after 28 d of supplementation loading (6.4 g·d −1 ) with β-alanine ( n = 7) or a placebo ( n = 7), and after a 5-wk supervised, SIT program performed twice weekly (repeated 1-km cycling sprints) while maintaining supplementation with β-alanine (1.2 g·d −1 ) or a placebo. Results: After the loading period, sprints 3 and 4 of the 4 × 1-km sprint intervals were improved with β-alanine supplementation (4.5% ± 3.4% and 7.0% ± 4.0%; P < 0.05, respectively). After 5 wk of SIT, training intensity increased in both groups but the change was greater with β-alanine supplementation (9.9% ± 5.0% vs 4.9% ± 5.0%; P = 0.04). β-alanine supplementation also improved supramaximal cycling time to exhaustion to a greater extent than placebo (14.9% ± 9.2% vs 9.0% ± 6.9%; P = 0.04), whereas 4- and 10-km TT performance improved to a similar magnitude in both groups. After SIT, β-alanine also increased anaerobic capacity (5.5% ± 4.2%; P = 0.04), whereas V˙O2peak increased similarly in each group (3.1% ± 2.9% vs 3.5% ± 2.9%; P < 0.05). Conclusions: These findings indicate that β-alanine supplementation enhances training intensity during SIT and provides additional benefits to exhaustive supramaximal cycling compared with SIT alone.